‘Doctor Brides’: A narrative review of the barriers and enablers to women practising medicine in Pakistan - Qazi, Muhammad Abdullah; Schofield, Susie; Kennedy, Catherine (Journal of the Pakistan Medical Association, 2021)
The current literature review was planned to explore the current issues and historical aspects of the problems faced by female medical students and doctors in Pakistan. The literature search comprised PubMed, Education Resources Information Centre and Google Scholar databases to look for resources from education as well as from health sector from 2009 to 2020. Due to lack of local literature on the subject, it was tried to make sense of the career barriers and enablers they face considering the underlying theory and evidence from other countries. Keeping the Pakistani context in view, it explored the interventions adopted in other countries to help reduce the gender-based issues which have resulted in the facilitation of women in health education and healthcare systems. The major gender issues identified were unequal representation of female doctors in leadership positions and in some specialties, work-life imbalances, socio-cultural norms and lack of professional development opportunities. Continuous...